MADRASAH NIZAMIYAH: Simbol Patronase Penguasa Sunni dalam Lembaga Pendidikan - Ahmad Ta'rifin (IAIN Pekalongan, 2010)
Nizam al-Mulk, vizier of Seljuq dynasty, had built severalmadrassas which were completed with libraries with a number ofendowments as sources of funds.Madrassas known as Madrasah Nizamiya were intended as the centerof the Sunni sect development, especially Syafi’iyah and Ash’arite.For that purpose, goals, curriculum and teaching activities are submittedto figures from the school’s leading scholars, among them are AbuIshaq al-Syirazy, Imam al-Haramayn and al-Ghazali, who respectivelyever held the Madrasah Nizamiya. The progress of MadrasahNizamiya is closely associated with the patronage of Nizam al-Mulkas the ruler of the dynasty of Abbas. Although Madrasah Nizamiyahwere related to the patronage of rulers - and then disappeared - themadrassa system as an institution of higher Islamic education wascontinued by the leaders of the later ruler with a similar patronage